SOCIAL LIMMINALITY AS THE STATIONARY STATE OF TRANSITIVE SOCIETIES IN GLOBALIZED WORLD - Орденов, С. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction The integration processes in societies of the traditionalist type are accelerated in the conditions of globalization. The process of involving of traditionalist societies into civilization is called overhauling modernization. Modernist modern societies themselves are considered as transient or transitive. At the same time, such modernization is not organic for traditionalist societies, since they lack the internal factors of civilization development. The aim and tasks of the article are to analyze the reasons for establishing social liminality as a stationary state of transitive societies in a globalized world. Research methods. The methodological basis of the study is the theoretical principle of intersubjectivity, in the context of the correlation of linear and nonlinear logic, understanding of the interconnection and interpenetration of the principles of objectivity and subjectivity, with further awareness of the tendencies of absolutisation in the philosophical comprehension of the phenomenon of globalization. Research results. Under the conditions of universal generalization of relations, the model of global capitalism is the main instrument of integration. Given that the human society has always been a set of social entities with different levels of development of social relations, and the modern global world – a multicultural conglomerate, the interaction in it takes place in two directions: the communicative (between developed capitalist countries), and expansive (the third world countries). This forces transitive societies to adapt to the global model of capitalist relations through incremental social transformations. In turn, these in-depth transformations cause divergent changes in adaptive societies, which make impossible their social development and structural adjustment, thereby institutionalizing the transition as a limminality phase, which becomes a certain type of their stationary state. Discussion. The scientific developments of G. Almond, S. Verby, V. Gelman, R. Inglehardt, H. Linz, S. Lipset, J. Stiglitz are devoted to the problems of social reforming of transitive societies. Researchers point to the existence of a stable correlation between existing social conditions in society and the assimilation of advanced socio-cultural norms and values. The problem of reforming of transitive societies is also related to the inactivity of the cultural sphere. In particular, it is stressed the fact that the imitative models of thinking in transitive societies continue to operate after transforming their institutional and organizational structure, which leads to the formation of hybrid models of socio-cultural constructs and destructive forms of social practices. E. Moren states that the policy of creating a planetary imperial hegemony, rather than a confederation of civilizations, was chosen to build a global society. The very idea of global "development" included a technical and economic component alone, quantitatively measured by indicators of growth and income, and does not include a humanistic aspect at all. This means that we must return to the policies of the mankind, internationalization and solidarity of the inhabitants of the entire planet, but this also means that there is a need and the return to the humanities of the status appropriate to them. Conclusion. As the study showed, globalization is a project of an integrated process of consolidation of the mankind, homogenization of the world and the formation of global consciousness. The integrative aspect of this globalization project is key, and the model of global capitalism is the instrument of its realization. At the same time, Western model of global capitalism in the course of its implementation by non-Western-type societies definitely undergoes hybridization, transforming towards a regulated market that corresponds to their hierarchical system of paternalistic relations. In turn, this leads to a series of adaptive transformations within traditionalist societies, turning them into transitive societies of catching upgrading, and preventing the structural rearrangement of these societies on a liberal basis, thus institutionalizing the transition as a limiting phase to become a certain type of a stationary state